Narrative Explorations of EFL Learners’ Engagement with AI Tools in Developing Writing Proficiency - Najmiah, Lailatun; Al-Anbari, Alaa Hussein Jafar (DUTIES: Education and Humanities International Journal, 2025)
This study explores the lived experiences of English as a Foreign Language (EFL) learners engaging with Artificial Intelligence (AI) tools to support their academic writing development. Using a narrative inquiry approach, the research investigates how learners describe their interactions with AI technologies such as ChatGPT and Grammarly, and what challenges and opportunities they perceive. Eighteen university-level EFL students participated in in-depth interviews, revealing that AI tools are widely appreciated for enhancing linguistic accuracy, improving efficiency, boosting writing confidence, and supporting idea generation. These benefits align with the Technology Acceptance Model and Sociocultural Theory, suggesting that AI acts as both a facilitator of ease and a scaffold within learners’ Zones of Proximal Development. However, the findings also highlight substantial concerns related to academic integrity, over-reliance, and AI’s limitations in generating culturally nuanced or critically engaging content. This duality reflects the "Paradox of Assistance," where the same features that make AI valuable can also inhibit deeper learning if uncritically used. The study emphasizes the need for intentional, pedagogically guided integration of AI in EFL writing instruction, promoting a balanced Human-AI collaboration that empowers learners as autonomous and reflective writers.